A view support for dendrobium nobile cultivation - YANG ZHONGPING (2018)
The utility model discloses a view support for dendrobium nobile cultivation, include the support frame, support the base, indulge support and lateral frame, supporting frame side wall is equipped with the controller, and support frame top sets up the roof, the roof rotates to connect indulges the support, and indulges the support bottom and fix inside supporting the base, support the inside watercatch bowl that is equipped with of base, indulge the leg joint lateral frame, and lateral frame external connection wire net, the planting box is connected to the wire net, and planting box lateralwall is equipped with the louvre, plant the inside gauze layer that is equipped with of box, and planting box back sets up the couple, the roof top sets up circulating water pump, and circulating water pump connects the water tank, the raceway is connected to the water tank. The utility model discloses the support has improved the ventilation effect of dendrobium nobile cultivation box, can satisfy the planting demand of d